The Developmental Narrative and Space as Salvation in the Works of Carl Sagan - Mix, Lucas John (Zygon, 2025)
Carl Sagan frames humanity’s future in space as a secular narrative of salvation. He aligns technical advancement with ethical growth. He presents an evolutionary epic, with humans growing up and going up to the stars, identifying space travel with species adulthood. His works Cosmos, Broca’s Brain, and Pale Blue Dot develop this theme to promote space travel and foster hope for the future. The biological terms, however, reflect outdated science, particularly theories of progressive evolution, deemed both unproductive and ethically problematic by biologists. The narrative owes more to a mythology of progress than to biology as science. Viewing it through the lens of religion helps reveal its contours and effects, allowing both proponents and opponents to understand it better. In that light, alternative metaphors, such as space travel as pilgrimage, may better serve Sagan’s aspiration of scientifically motivated beliefs.